Indus potters in central Oman in the second half of the third millennium BC. First results of a technological and archaeometric study - Méry, Sophie (Proceedings of the Seminar for Arabian Studies, 2017)
The nature of cultural interactions between the Indus Civilization and Magan is explored in this paper. The presence of Indus potters in eastern Arabia can now be demonstrated based on a combined technological and petrographical study of a range of pottery types found at the site of Salūt ST1 (Sultanate of Oman). Similar discoveries from other Umm an-Nar sites in the Sultanate of Oman and the UAE supports the hypothesis that Indus communities were living alongside the Magan people at Umm an-Nar sites more extensively than previously thought.